2018
DOI: 10.1039/c8nr04078h
|View full text |Cite
|
Sign up to set email alerts
|

Hetero-biicosahedral [Au24Pd(PPh3)10(SC2H4Ph)5Cl2]+ nanocluster: selective synthesis and optical and electrochemical properties

Abstract: A recent study implied that a hetero-biicosahedral 25-atom cluster composed of two kinds of icosahedral 13-atom clusters could serve as a molecular rectifier and dipole material. However, no hetero-biicosahedral 25-atom clusters containing three types of ligands, in this case, phosphines, halogens, and thiolates, have been reported. In this study, we selectively synthesized [Au24Pd(PPh3)10(SC2H4Ph)5Cl2]Cl (Au = gold, Pd = palladium, PPh3 = triphenylphosphine, SC2H4Ph = phenylethanethiolate, Cl = chloride), in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 102 publications
1
65
0
Order By: Relevance
“…[30][31][32][33][34][35][36][37][38][39]41] Similar researchh as recently been undertaken by several groups,a nd their findings have demonstrated that the mixing( alloying) of heteroelements is an extremelye ffective means to modulate the electronic structure and functions of NCs. [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] In addition,…”
Section: Purpose Of This Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32][33][34][35][36][37][38][39]41] Similar researchh as recently been undertaken by several groups,a nd their findings have demonstrated that the mixing( alloying) of heteroelements is an extremelye ffective means to modulate the electronic structure and functions of NCs. [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] In addition,…”
Section: Purpose Of This Reviewmentioning
confidence: 99%
“…[211] Negishie tal. [77] synthesized [Au 24 Pd(PPh 3 ) 10 (PET) 5 Cl 2 ] + containing one Pd atom in 2018. [62] (B) [Au 25Àx Ag x (PPh 3 ) 10 (PET) 5 Cl 2 ] 2 + (x = 2-13), [62] (C) [Au 23 Ag 2 (PPh 3 ) 10 (PET) 5 Cl 2 ] 2 + , [103] (D) [Au 24 Cu(PPh 3 ) 10 (PET) 5 Cl 2 ] 2 + , [103] (E) [Au 25Àx Cu x (PPh 3 ) 10 (PET) 5 Cl 2 ] 2 + (x =~3.77), [211] and (F) [Au 24 Pd(PPh 3 ) 10 (PET) 5 Cl 2 ] + .…”
Section: Au Nàmentioning
confidence: 99%
“…Our group prepared a series of alloy rod‐like Au 25‐n M n nanoclusters, including [Au 12 Ag 13 (PPh 3 ) 10 (SC 2 H 4 Ph) 5 Cl 2 ] 2+ , [Ag 1 Au 24 (PPh 3 ) 10 (SC 2 H 4 Ph) 5 Cl 2 ] 2+ and [Cu 1 Au 24 (PPh 3 ) 10 (SC 2 H 4 Ph) 5 Cl 2 ] 2+ via the metal‐exchange and single foreign atom‐doping strategies . Recently, Negishi and co‐workers prepared the rod‐like [Pd 1 Au 24 (PPh 3 ) 10 (SC 2 H 4 Ph) 5 Cl 2 ] + with size‐focusing method . The structures of all the aforementioned NCs have been well characterized by SCXRD or determined by theoretical calculations.…”
Section: Resultsmentioning
confidence: 99%
“…To verify this assumption, we carriedo ut DFT calculations on the A-(B) n -A and B-(A) n -B model NCsa tt he PBE [41,42] /DNP-ECP level of theory.T or educe computational costs, -SMe and PMe 3 were used as model ligandsi na ll clusters, an economy validatedi nr ecent studies. [28,[44][45][46][47][48] The geometry optimization of Ag 38 , Ag 46 , Ag 63 ,a nd Ag 67 startedw ithas implified structure of the reported single-crystal X-ray structures, whereas the startingg eometries of Ag 25 , Ag 88-a ,a nd Ag 88-b were constructed by using theoretical modeling software (according to the aforementioned atomic arrangement rules). The results of these calculations not only verified the proposed frameworks of…”
Section: Structure Of Ag 67mentioning
confidence: 99%